Towards A Competitive Manufacturing Sector - Rajiv Kumar; Abhijit Sen Gupta (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The Indian manufacturing sector has grown at an impressive average rate of 9.5 per cent annually since 2003-04. Its sustained growth is crucial for generating employment opportunities needed to absorb the rapidly expanding workforce. In this context, this paper reviews the current state of the sector and focuses on determinants of its competitiveness. The paper finds that Indian manufacturing sector exhibits a great deal of regional variation and a marked dualism between the organized and the unorganized segments in terms of both productivity and wage levels. The level of labour absorption in the organized manufacturing sector has been weak as reflected in the declining labour intensity in this sector. This does not augur well for achieving inclusive growth. We also find that although there have been significant changes in the composition of exports in the last 20 years; India is still a very small player at the global level, especially in knowledge intensive and advanced technology products. Finally, the paper explores India's potential for transforming itself into a hub of mass manufacturing. We find that the main constraints in doing so have been the low level of R&D, relative lack of skilled personnel and relatively low FDI levels.
Keywords: L60; O11; 330; manufacturing; competitiveness; mass manufacturing; Internationaler Wettbewerb; Branchenentwicklung; Industrie; Standortfaktor; Indien